ByzRev 07.2025.068: Stephen Mitchell, The Christians of Phrygia from Rome to the Turkish Conquest: (Ancient Judaism and Early Christianity 117; Early Christianity in Asia Minor 4). Leiden: Brill 2023. - Sitz, Anna (The Byzantine Review, 2025)
Stephen Mitchell, The Christians of Phrygia from Rome to the Turkish Conquest (Ancient Judaism and Early Christianity 117; Early Christianity in Asia Minor 4). Leiden: Brill 2023. xxiii+698 pp., 77 figures, and 15 maps. – ISBN 978-90-04-54637-0